2017
DOI: 10.5830/cvja-2017-017
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile, management and outcomes of patients with pulmonary embolism: a retrospective tertiary centre study in Angola

Abstract: SummaryObjective:Pulmonary embolism (PE) is a potentially fatal disease. In Angola, few data are available on its occurrence. The aim of the study was to characterise the clinical profile, management and outcomes of patients with PE.Methods:A retrospective observational study was conducted at the Girassol Clinic in Luanda, Angola. The medical records of patients admitted to the intensive care unit were analysed from 2011 to 2015.Results:Fifty patients were included and the median age was 50.5 ± 17.8 years. Dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…The most common ECG finding was sinus tachycardia (cases 2, 3 &5) followed by the characteristic feature of large S wave in lead1, pathologic Q wave in lead III, and inverted T wave in lead III (SIQ3T3) (cases 1&3). This is similar to the finding in the Angola study (4). The most common abnormality on the echocardiogram was left ventricular hypertrophy (cases 1, 3 &4).…”
Section: Figures 7 and 8: The Chest Ctpa For The Patient In Case 5 DIsupporting
confidence: 88%
See 3 more Smart Citations
“…The most common ECG finding was sinus tachycardia (cases 2, 3 &5) followed by the characteristic feature of large S wave in lead1, pathologic Q wave in lead III, and inverted T wave in lead III (SIQ3T3) (cases 1&3). This is similar to the finding in the Angola study (4). The most common abnormality on the echocardiogram was left ventricular hypertrophy (cases 1, 3 &4).…”
Section: Figures 7 and 8: The Chest Ctpa For The Patient In Case 5 DIsupporting
confidence: 88%
“…The most common abnormality on the echocardiogram was left ventricular hypertrophy (cases 1, 3 &4). This finding shares no similarity with other studies in which right atrial enlargement and right axis deviations were the two most common ECG findings (3,4,7,13). However, it is an important tool in the investigation and management of PE 4 .…”
Section: Figures 7 and 8: The Chest Ctpa For The Patient In Case 5 DIsupporting
confidence: 57%
See 2 more Smart Citations
“…Recent studies on the continent have reported more cases, but the limited resources, especially the access to CTA, still contribute to the reduced number of PE cases reported[16] [17][18] [19] …”
mentioning
confidence: 99%